Revision of Russula genus in Kosovo: new records and ecological insights - Qendrim Ramshaj; Mitko Karadelev (Acta Biologica Slovenica)
Among its members, the genus Russula is one of the largest ectomycorrhizal genera, with approximately 1,300 recognized species. Previous studies on macrofungi in Kosovo have documented 25 species, primarily from oak forests. This study adds 14 new species to the mycobiota of Kosovo, bringing the total number of Russula species documented in the country to 39. With the exception of R. torulosa, which was found at two locations, all other newly recorded species were observed at a single site. Additionally, new location records for previously known species are presented.